Analysis of Decision Number 40/Pdt.P/2022/PA.Tgr Concerning Good Faith In Polygamy Without Court Permission - Abdul Mujib; Mochamad Cholil (IHSA Institute, 2026)
This study aims to analyze the application of legal provisions concerning polygamy licensing and the principle of good faith in polygamous marriages performed without court permission, specifically focusing on the legal considerations in the Tenggarong Religious Court Decision Number 40/Pdt.P/2022/PA.Tgr. The research employs a normative juridical methodology with statutory, case-based, historical, and conceptual approaches to evaluate primary and secondary legal materials gathered through literature review. The findings reveal that the petitioners’ marriage constitutes unauthorized polygamy that violates the mandatory requirements of Law No. 16 of 2019 and the Compilation of Islamic Law, as it was conducted without judicial approval or the first wife's consent. The court's analysis determines that the parties' decision to proceed with a secret marriage despite being aware of legal impediments serves as a definitive indicator of bad faith (malafide). Consequently, the panel of judges rejected the petition for marriage validation to prevent the creation of a negative precedent that could encourage the abuse of illegal polygamy and undermine legal certainty. This study concludes that strict adherence to procedural requirements and the principle of good faith are essential to maintaining the integrity of the marriage institution and protecting the rights of all parties involved.